2021
DOI: 10.1021/acsomega.1c03414
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles Coupled with Graphene Nanoplatelets Modified Screen-Printed Carbon Electrodes for Rhodamine B Detection in Food Products

Abstract: A rapid, simple, and sensitive voltammetric sensor has been fabricated to determine Rhodamine B (RhB), a textile coloring agent. Silver nanoparticles (AgNPs) were synthesized by the chemical reduction method of silver nitrate and sodium citrate. Graphene nanoplatelets (GPLs) and AgNPs were drop-casted on the surface of a working electrode of a screen-printed carbon electrode (SPCE), forming the SPCE-GPLs/AgNPs samples. Scanning electron microscopy−energy dispersive X-ray and cyclic voltammetry confirmed the al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Table 1 provides a comparison of the optimised DPV method with previously reported analytical methods for the determination of Rhodamine B. The linear range for the method is comparable to that reported by high performance liquid chromatography following solid phase extraction [17] and that recorded for modified SPCEs [29]. The quoted limit of detections for the spectroscopy-based approaches [67,70,73] are lower than those for the voltammetric method developed here, however, these necessitate time-consuming, complex sample pre-treatment steps.…”
Section: Effect Of Ascorbic Acid On Rhodamine B Differential Pulse Vo...mentioning
confidence: 59%
See 2 more Smart Citations
“…Table 1 provides a comparison of the optimised DPV method with previously reported analytical methods for the determination of Rhodamine B. The linear range for the method is comparable to that reported by high performance liquid chromatography following solid phase extraction [17] and that recorded for modified SPCEs [29]. The quoted limit of detections for the spectroscopy-based approaches [67,70,73] are lower than those for the voltammetric method developed here, however, these necessitate time-consuming, complex sample pre-treatment steps.…”
Section: Effect Of Ascorbic Acid On Rhodamine B Differential Pulse Vo...mentioning
confidence: 59%
“…The results shown in Table 2 indicate that the method gives reliable results using an external calibration method. The analytical performance characteristics were better than those reported at a glassy carbon electrode [28] and an Ag nanoparticle modified screen-printed electrode [29]. It was also shown possible to determine Rhodamine B via cyclic voltammetry using the same SPCE over the range 0.50-1025 µgmL −1 (R 2 = 0.9929).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…As an alternative, a carbon-based electrode is generally used. [14][15][16][17] It is imperative to note that a bare electrode, such as carbon, platina, or gold electrode, usually exhibits a relative low electrochemical response to an analyte. Therefore, the modulation of the electronic structure on the electrode surface is required to improve the current response.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the modulation of the electronic structure on the electrode surface is required to improve the current response. 14,[18][19][20][21][22][23]55 Studies have shown that a bismuth-modied carbon paste electrode exhibits excellent performance in tracking heavy metal ions at a low concentration, as suggested by a greater current response in comparison to a bare carbon paste electrode. 18,20,21 A polymer containing an ion template and a functional monomer is called as an ion-imprinted polymer (IIP).…”
Section: Introductionmentioning
confidence: 99%